Analisis Kendala Penerapan Otomasi Perpustakaan Di Perpustakaan Perguruan Tinggi Bina Sriwijaya Palembang - Mutiarani, Riska; Yoanda, Sely; Gunaidi, Aang (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2022)
This study discusses the constraints of the Bina Sriwijaya library. This study aims to identify the problems faced by librarians that cause the library has not implemented automation. This study uses a qualitative approach with a descriptive method. Data collection techniques used in this study were observation and interviews with the head of the library Bina Sriwijaya. The types and sources of data needed in the study are primary data and secondary data. In this study, researchers took 1 informant, namely the head of the library. Data collection techniques in this study, the authors use two ways, namely: library research and field research, namely direct research that is carried out directly on the object under study by means of: observation, interviews, and documentation. The data processing and analysis techniques. The data processing and analysis technique in this research is qualitative data analysis, which is a non-statistical technique. There are three steps of qualitative data processing, namely: data reduction, data presentation and drawing conclusions/verification. Based on the results of the study, there are several obstacles behind the Bina Sriwijaya College library which has not used the SLiMS application in its library, namely human resources and funding problems.